Analysis of the Electromagnetic Effect Mechanism of EED under Continuous Wave Radiation - Biao Wang; Yongwei Sun; Shuai Zhou; Xiaojian Li; Nan Li; Zhiyou Fan; Ying Xiong; Tiannan Wang (International Journal of Antennas and Propagation)
The electromagnetic radiation sensitivity of the electric explosive device (EED) and its installed use state is closely related to the size of the equipment and radiation field strength constraints. The use of the traditional all-level electromagnetic radiation method for the effect of the actual installed EED test in the electromagnetic environment simulation encountered a technical bottleneck. The microwave band is difficult to effectively assess through the current standing wave distribution and skin effect. The temperature rise of the EED bridge wire has no relationship with the frequency of the electromagnetic wave. In this paper, through the analysis of the electromagnetic effect mechanism of the EED, the coupled power model of electromagnetic irradiation of the EED is obtained, and the relationship between the temperature rise of the bridge wire of the EED and the electric field strength model is established. Under the action of high-frequency continuous waves, the electromagnetic effect of the device is tested to verify the correctness of the mechanism analysis of the electromagnetic effect of the device under the action of continuous waves. The results provide crucial technical support for the electromagnetic protection of the device under the harsh electromagnetic environment of the battlefield.